Analysis of Students' Mathematic Analisis Kemampuan Koneksi dan Pemahaman Konsep Matematis Siswa - Efrata Gee; Darmawan Harefa (Musamus Journal of Primary Education, 2021)
The research aims to describe the connection skills and understanding of students' mathematical concepts, especially in cube and block material. The study took a qualitative approach and used descriptive research. The findings of this research show some of the students still have difficulty understanding the concept of cube and block material. The students are still confused in choosing what procedures (formulas) to use in solving test questions, and the students still have difficulty applying the concept of cubes and blocks in working on problems. Furthermore, for the mathematical connection ability, students did not understand the relationship between the concept of cubes and blocks. This is because students do not understand the test questions and have mastered the previous prerequisite material that relevant to the questions. The students' accuracy in doing arithmetic operations often makes calculation errors. The conclusion is the students' ability to connect and understand mathematical concepts is still low.